English Teaching Assistant Program for Elementary School Teachers - Farah, Rafika Rabba; Khoiriyah, Khoiriyah; Wicaksono, Bayu Hendro (Universitas Pendidikan Ganesha, 2024)
To help the teaching and learning process, community service is carried out in two programs: designing digital student workbooks and assisting English language learning by integrating English for Young Learners activities. This study aims to report on implementing the English teaching assistant program for elementary school teachers. Descriptive research is used to describe activities that are expected to improve the teaching and learning process in the two partner schools. The subjects of this research were three elementary school teachers and six volunteer teachers from Indonesian students. This type of research is qualitative research. In collecting data, this research used interview and observation methods. The instruments used in this research include a list of interview questions for elementary school teachers and observation sheets to record the activities of English teaching assistants in the classroom. The approach used is descriptive because this research aims to describe an existing phenomenon: the English teaching assistant program for elementary school teachers at the Kuala Lumpur Indonesian School. Thus, the results of implementing the program show that community service has been carried out effectively to meet the needs of partner schools. Furthermore, teachers and school coordinators highlighted their positive feedback regarding the program results, indicating that the project team was successful in implementing the teaching assistant program in partner schools. In this way, the intended program presented to the community can be implemented effectively and is expected to continue in future partnerships.